Composing the North: A Musical Study of Identity, Transformation, and Reflection - Stanovic, Adam (Nordlit, 2020)
In 2015, occursus – a network of artists, researchers, and academics with an interest in space and spatialities in art – commissioned a series of musical compositions based on a small patch of land close to the centre of Sheffield, England. The land in question, which houses one of the world’s oldest cementation furnaces, has witnessed a remarkable period of transformation; initially standing among some 2,500 furnaces in the heart of the industrialised city centre, the national decline of steel production resulted in dereliction and for much of the past sixty years the furnace towered over wasteland. occursus acquired the land in 2012, and turned it into a community arts space, now known as Furnace Park. This article explains how a series of composers responded to this park through the creation of new musical works. Although most attention is directed to the author’s own work, Foundry Flux (2015), the primary focus of the article is on the collective approach to occursus’ objectives which, to the surprise of all of the commission-holders, focused their attention way beyond the tiny patch of land in the heart of Sheffield; the project became a catalyst for: 1) studying the identity of the city; 2) observing and initiating transformations of that identity; and 3) reflecting upon one’s own role within such identity transformations. In combining these three, those in the group found themselves engaged in a practical process of composing the north.